2018
DOI: 10.4254/wjh.v10.i12.898
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus-associated hepatocellular carcinoma after sustained virologic response

Abstract: The introduction of a direct-acting antiviral (DAA) for patients with hepatitis C virus (HCV) infection, could lead to higher sustained virologic response (SVR) rates with fewer adverse events, and it could shorten the treatment duration relative to the interferon era. Although most recent clinical studies have demonstrated that the occurrence rates of hepatocellular carcinoma (HCC) are decreased by SVR with both interferon-based and interferon-free-regimens, there are several reports about the unexpected obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Additionally, ~70% of HCC cases are caused by HBV and/or HCV infection. Although nucleos(t)ide analogs and direct-acting antivirals can control HBV and HCV replication, HCC occurrence is occasionally observed [49,50,51], and better biomarkers for early detection of HCC are needed. Furthermore, genetic and epigenetic factors, such as miRs, are involved in liver cirrhosis and its progression to HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, ~70% of HCC cases are caused by HBV and/or HCV infection. Although nucleos(t)ide analogs and direct-acting antivirals can control HBV and HCV replication, HCC occurrence is occasionally observed [49,50,51], and better biomarkers for early detection of HCC are needed. Furthermore, genetic and epigenetic factors, such as miRs, are involved in liver cirrhosis and its progression to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HBsAg-positive HCV-coinfected patients with liver cirrhosis are at a high risk of developing HCC [45], with elevated ALT levels [46] and hepatic steatosis [47] risk factors for the development of HCC in patients with HCV-related liver cirrhosis. SVR can reduce HCC development in most patients infected with HCV-related liver cirrhosis [48], although changes in the risk of HCC development following HCV eradication with direct-acting antivirals (DAAs) is controversial [49,50,51]. Further studies will be needed in DAA-era.…”
Section: Liver Cirrhosis and Its Progression To Hcc With Hcv Infecmentioning
confidence: 99%
“…On the other hand, the study of Yoo et al 12 on 574 HCV patients receiving direct-acting antiviral therapy for at least 24 weeks, found that the cumulative HCC incidence was 0.47%. Unfortunately, these two studies didn't report the percentage of cirrhosis patients according to the Metavirscore.Multiple mechanisms for the occurrence of HCC and rapid immune changes have also been documented, includes cytokines and chemokines during and following DAA therapy 13 .…”
Section: Resultsmentioning
confidence: 99%
“…Patients with advanced stages of liver damage caused by the infectious inflammatory HCV processes may continue to present an important risk for progression of the fibrotic condition and development of HCC, even after clearance of the viral infection. SVR can reduce the risk of developing HCC in most patients with HCV-related liver cirrhosis; however, some studies have reported an increased and recurrent rate of HCC in patients with HCV cirrhosis who had been treated with DAAs [ 39 , 40 , 41 ]. The mechanisms underlying these events are not fully understood [ 42 ].…”
Section: Discussionmentioning
confidence: 99%